SystemCraft - a primer: How to Tackle our Toughest Problems - Simpson, Kate; Randall, Ian (Wasafiri, 2020)
Systemcraft is our applied framework to help leaders and organisations get started and keep going when faced with complex problems. It is built on our practical experience. It draws on a broad body of research, action and theory from the worlds of complexity thinking, systems theory, adaptive management, leadership development, social movements, development theory and beyond. Systemcraft has been designed to make systems thinking something any leader can apply when they find themselves faced with a complex problem and asking, ‘So what do I do next?’

System Innovation Network - Si Network (Si Network, 2020)
The Si Network is an online platform for building the developing of systems innovation - connecting people around the world to learn and apply the ideas and methods of systems innovation towards addressing complex challenges and building better systems that work for all. Not sure what systems innovation is? Systems innovation is a new approach to innovation that tries to tackle complex social and environmental challenges through the use of more holistic & innovation driven approaches. It is a kind of innovation that aims to change the underlying structure of a system, thus potentially enabling a more transformational kind of change - systems change - rather than incremental "innovation as usual". What Do You Do? We are building an ecosystem of individuals and organizations co-learning and co-creating systems innovation across geographies and sectors. This ecosystem is enabled by our online platform which provides educational content, toolkits, organizes events and projects as well as provides various support services for organizations. Purpose Statement Our purpose is to build the world’s capacity for systems innovation - so as to better understand and address complex challenges and co-create a world where systems work for all. We envision a world where everyone thinks in systems and has an understanding of complex systems. From this understanding, we are able to design and develop regenerative systems that work for everyone. Our mission is to grow the field of systems innovation as a pathway to co-learn the ideas of systems thinking and apply them to co-creating new systems Who's Involved? We are a networked organization of some 17K+ members forming part of 20+ hubs in major cities around the world. Our community is broad and diverse in areas of work and interest from designers, innovators, and entrepreneurs, to researchers and management but they all share a common interest in learning and applying systems thinking ideas. The Si platform is developed and managed by a small core team based in London UK. We are registered as a business but operate as a social enterprise focused on our purpose of advancing the area of systems innovation in theory and practice. Core Value Creativity - We put creativity at the centre of what we do. Holding a space for curiosity, diversity of views, exploration and critical thinking as a pathway to transformative innovation. Openness - We strongly believe in openness in our ways of being, thinking and organizing as a sustainable pathway to creating an adaptive, scalable and dynamic community. Growth Mindset - We embrace challenges as opportunities for continuous personal and collective learning and development, with a never-ending potential to grow and start with a new beginning. Perseverance - When facing uncertainty and failure, perseverance is what is needed to maintain commitment and a resilient pathway aligned with our purpose. Care - Care is one of our core principles. We foster relationships based on honesty and empathy, striving to be present and conscious in what we do and taking responsibility for the effects of our actions.